2019
DOI: 10.1155/2019/8129648
|View full text |Cite
|
Sign up to set email alerts
|

The Quality Control of Tea by Near-Infrared Reflectance (NIR) Spectroscopy and Chemometrics

Abstract: Tea is known to be one of the most popular beverages enjoyed by two-thirds of the world’s population. Concern of variability in tea quality is increasing among consumers. It is of great significance to control quality for commercialized tea products. As a rapid, noninvasive, and nondestructive instrumental technique with simplicity in sample preparation, near-infrared reflectance (NIR) spectroscopy has been proved to be one of the most advanced and efficient tools for the control quality of tea products in rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 60 publications
0
27
0
2
Order By: Relevance
“…Visible/near-infrared spectroscopy (VNIRS) is widely used as a rapid and non-destructive technique for tea classification [6][7][8] and tea composition determination [9][10][11]. Hyperspectral imaging (HSI) is a technique integrating both spectroscopic techniques and imaging techniques, acquiring spectral and spatial information simultaneously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visible/near-infrared spectroscopy (VNIRS) is widely used as a rapid and non-destructive technique for tea classification [6][7][8] and tea composition determination [9][10][11]. Hyperspectral imaging (HSI) is a technique integrating both spectroscopic techniques and imaging techniques, acquiring spectral and spatial information simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…In general, a certain amount of tea samples (contains tens or more tea leaves in a sample) is used for VINRS and HSI analysis and overlap of tea leaves occurs in this situation [6][7][8][9][10][17][18][19]. Thus it is difficult to identify adulterations in this amount of tea when some amounts of adulterations are mixed into the normal sample.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the recently reported approach showed that recovery of parameters in a multi-wavelength time-resolved data can be achieved without prior instrument calibration [47]. Other notable NIR innovations in instrumental methods for spectral analysis during the review period includes a dual detection channel instrument for NIR time-resolved diffuse optical spectroscopy [48], functional NIR spectroscopy (fNIRS) instruments for high-density diffuse optical tomography [49,50], and other NIR-based sensors [51][52][53][54][55].…”
Section: Portable Nir Sensorsmentioning
confidence: 99%
“…The tea plant [ Camellia sinensis (L.) O. Kuntze], cultivated for the production of non-alcoholic beverages, is an economically important woody crop worldwide ( Zhu et al, 2017 , 2019 , 2020b ; Yang et al, 2019 ). Leaf color is an important agronomic trait of this plant.…”
Section: Introductionmentioning
confidence: 99%